The lengths of the fibres of Henle in the retina of macaque monkeys: implications for vision. - Perry, V; Cowey, A (1988)
In Golgi preparations of retinae from macaque monkeys the lengths of the fibres of Henle from photoreceptors, and Müller's fibres were measured. It was shown that the lengths of Müller's fibres provide a good estimate of the lengths of adjacent fibres of Henle of photoreceptors. The fibres form a radiate pattern with respect to the fovea. They are longest at the fovea and their length decreases in a systematic way with distance from the fovea. The implications of the fibre length are considered with respect to the relationship between the ganglion cell distribution and central magnification factors. We show that even when the functional offset introduced by the fibres of Henle and by bipolar and ganglion cells is taken into account there is not a constant proportional relationship between ganglion cells and central magnification factors. The representation of the central few degrees of the visual field on the striate cortex is greater than would be predicted on the basis of the ganglion cell density for the central retina.